PRACTICE OF USING THE PELVIC C-CLAMP IN PATIENTS WITH SEVERE CONCOMITANT PELVIC INJURY - I. V. Kazhanov; V. A. Manukovskii; I. M. Samokhvalov; G. M. Besaev; S. I. Mikityuk; V. G. Bagdasariants (Вестник хирургии имени И.И. Грекова)
The  OBJECTIVE  the  study  is to rate  the  clinical efficacy  of pelvic C-clamp  in patients with unstable pelvic ring injuries  and signs  of intrapelvical  ongoing  bleeding. MATERIAL AND METHODS.  We  studied the  results of treatment of 87  patients with unstable pelvic  ring injuries signs  of unstable hemodynamics. Pelvic  C-clamp  was  used for mechanical stabilization of the  posterior pelvic  half-ring  in order  to stop  the  ongoing  pelvic  bleeding. Surgical methods of hemostasis in addition to  the  stabilization of the  pelvis  were  used in 30  patients. Control  of systolic  blood  pressure in the  dynamics,  volume and   duration   of  blood   transfusion  therapy  were   carried   out  to  assess the   effectiveness  of  hemostasis.  Additionally, spiral computed tomography with intravenous contrast enhancement and pelvic diagnostic angiography were performed. RESULTS.   Surgical   methods of  hemostasis  combined with  mechanical  stabilization of  the  damaged pelvic  ring  made allow  to  achieve the  final  stopping of  the  ongoing   pelvic  bleeding in  ¾   patients. CONCLUSION. In severe concomitant pelvic  injury,  surgical   methods of  hemostasis in  combination with  mechanical  stabilization of  the  damaged pelvic  ring should   be  actively  used in  patients in  critical  condition.